2014
DOI: 10.1007/s00701-014-2288-1
|View full text |Cite
|
Sign up to set email alerts
|

Interdigital direct neurorrhaphy for treatment of painful neuroma due to finger amputation

Abstract: Although this study was based on a small number of patients, it indicates that interdigital neurorrhaphy seems to be a feasible surgical treatment for painful digital neuroma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 33 publications
0
11
0
Order By: Relevance
“…Patients who experience a digit amputation have a reported 2.7% to 30% incidence of developing a symptomatic neuroma. 1,2 In a nerve injury where the axon is disrupted, the distal portion of the axon will undergo Wallerian degeneration. The proximal portion of the neuron sprouts toward the empty neural tube and will grow 1 to 2 mm per day to restore the nerve's function.…”
mentioning
confidence: 99%
“…Patients who experience a digit amputation have a reported 2.7% to 30% incidence of developing a symptomatic neuroma. 1,2 In a nerve injury where the axon is disrupted, the distal portion of the axon will undergo Wallerian degeneration. The proximal portion of the neuron sprouts toward the empty neural tube and will grow 1 to 2 mm per day to restore the nerve's function.…”
mentioning
confidence: 99%
“…All patients showed some temporary pain relief after nerve block, and therapeutic results were observed during later follow-up. Their findings indicated that interdigital neurorrhaphy achieved satisfactory improvement of symptoms and hand dysfunction [ 17 ]. Classical surgeries are mostly used in clinical practice and they can indeed provide a certain treatment efficacy.…”
Section: Resultsmentioning
confidence: 99%
“…Lidocaine is used in the vast majority of the blocks. [ 7 , 9 , 10 , 12 , 19 23 , 29 , 30 , 36 39 , 42 , 45 , 46 , 48 50 , 52 , 56 , 57 , 60 , 61 , 66 ] It is not known whether a block with a different local anaesthetic, like Bupivacaine[ 13 ] with a longer duration of action may increase the accuracy of prediction.…”
Section: Discussionmentioning
confidence: 99%